Antimicrobial Resistance Of Foodborne Pathogens In Stool Of Diarrhoea Patients In Two Selected Health Facilities And Food From Vendors In Selected Communities In Ghana - Dela, H. (University Of Ghana, 2021)
Foodborne pathogens (FBPs) have been implicated as the cause of so many food poisonings and outbreaks worldwide. Food borne bacteria are the second most common FBP after viruses in causing public health threat due to the gradual emergence of antimicrobial resistance (AMR) in the food chain. Although contaminated food is frequently implicated as the cause of diarrhoeal-related hospitalization, especially during outbreak investigations in Ghana, integrated surveillance has not been conducted to ascertain this fact. This study engaged the various transdisciplinary sectors in human and environmental health to show the holistic approach in understanding the occurrence of AMR of foodborne bacteria in Ghana. Stool of patients attending Maamobi General hospital and Kaneshie polyclinic were collected, and questionnaire administered to patients to understand the risk factors involved in diarrhoea transmission. Ready-to-eat (RTE) food and water were collected from food vendors, palm swabs of food vendors as well as responses on possible risk factors leading to food and water contamination were investigated. Common pathogens isolated in stool were E. coli, E. cloacae, K. pneumoniae in food, while K. pneumoniae, Aeromonas spp. and E. cloacae were isolated from food, water and palm samples from the Maamobi and Kaneshie communities. Among the stool isolates, a total of 69.7% (85/122) Enterobacteriaceae was recovered in the study with an overall ESBL occurrence of 26.5%, predominantly among E. coli (13.2%; 10/76), Klebsiella pneumoniae (35.7%; 5/14) and Proteus mirabilis (57.1%; 4/7). Among the ESBL genes detected, blaTEM (n=14) was common, followed by blaCTX-M (n=13) and blaSHV (n=4). Thirty-four E. coli isolates from the stool samples possessed the heat labile (Lt) gene of Enterotoxigenic E. coli (ETEC) in the stool samples. All the Enterobacteriaceae isolates were resistant to the penicillins and aminoglycosides apart from E. coli which showed reduced susceptibility to both drug classes. The food items showed the common occurrence of E. cloacae (16.8%), Citrobacter spp (10.1%), E. faecalis (7.8%), Pseudomonas spp (6.7%) and K. pneumoniae (4.0%). Resistance genes and Diarrhoeagenic E. coli (DEC) showed among two C. freundii isolates possessing the blaTEM gene and one E. coli possessing the Lt gene of ETEC. Over 50% resistance to penicillins and Rifampicin among most of the Enterobacteriaceae (E. cloacae, Citrobacter spp, Aeromonas spp), and non- Enterobacteriaceae (E. faecalis) were observed among the isolates recovered. Common pathogens recovered in water and palm were K. pneumoniae, Aeromonas spp. and E. cloacae with one K. pneumoniae isolate from the palm of a food vendor possessing the blaTEM gene. Resistance to majority of the antibiotics among the Enterobacteriaceae as well as non-Enterobacteriaceae (E. faecalis and Pseudomonas spp) was observed. Mean Total Plate Counts (TPC) of 1.4 X 105 CFU/g) of unsatisfactory interpretation was observed in stew as well as mean Total Coliform Counts (TCC) of 2.2 X 105 CFU/g and 1.7 X 105 CFU/g occurring in stew and ‘waakye’ respectively. Over 50% of all water types examined for mesophilic bacteria by TPC and TCC were considered impure with all palm swabs showing a 100% purity. Environmental samples (food and water) showed the effect of non-adherence to proper hand hygiene on food and water contamination during street food vending and the need for targeted education and enforcement of food safety policies in the country. These findings confirm the existence of AMR FBPs posing a threat to food safety due to the difficult to treat infections in case of transmission. Similar resistance to beta-lactams, Tetracyclines, Azithromycin and Penicillinase antibiotics among the clinical and environmental isolates shows common FBP transmission patterns which warrants the need for more AMR integrated surveillance in the food chain prior to consumption.
PhD. Applied Parasitology
Keywords: Ghana; Diarrhoea; Antimicrobial Resistance; Foodborne Pathogens; Vendors